Implementasi Metode Inquiry Based Learning dalam Pembelajaran Sains Anak Usia 5-6 Tahun - Dessy Farantika; Lely Putri Rahayu; Raras Ayu Prawinda (Alzam: Journal of Islamic Early Childhood Education, 2025)
Abstract: This study aims to describe the implementation of the Inquiry Based Learning method in science learning for 5–6-year-old children and to examine the development of their scientific abilities. This research used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results show that the Inquiry Based Learning method was applied in five main stages: questioning, observing, experimenting, analyzing, and concluding. Teachers designed lesson plans adapted to children's developmental characteristics and provided exploration space to encourage active participation. Evaluation was carried out authentically through process assessment. Children showed improvement in their ability to ask questions, experiment, and draw conclusions. These findings confirm that Inquiry Based Learning is effective in supporting early childhood science learning.